REBRANDING SOFYAN HOTEL CUT MEUTIA DALAM MENINGKATKAN CITRA - Andriani, Fizzy; Anandita, Camilla (JURNAL PUSTAKA KOMUNIKASI, 2019)
This was done as a form of continuous improvement in carrying out the best service. Sofyan Hotel also has a strong desire to refresh the brand image that has been done since the hotel stood. From this background, this study found a problem regarding the concept of rebranding conducted by Sofyan Hotel Cut Meutia in improving the image. This study uses a qualitative approach with the post-positivism paradigm. The method in this study is based on a case study. Data collection techniques using observation, interviews, researchers? views, and other secondary data sources in the library. The purpose of this study was to determine the concept of rebranding logos applied by Sofyan Hotel Cut Meutia in improving the image. The results of his research, researchers used the rebranding stage. The researcher concluded that the logo rebranding process had raised the image in the community. This can be seen from the activities and socialization of Sofyan Hotel Cut Meutia, which every month diligently holds promos and participates in collaboration with brands that share the same vision.